2001
DOI: 10.1046/j.1365-3024.2001.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitro susceptibility of hydatid cysts of Echinococcus granulosus to nitric oxide and the effect of the laminated layer on nitric oxide production

Abstract: Murine hydatid cysts of Echinococcus granulosus were incubated in vitro in the presence of nitric oxide produced from S-nitroso-N-acetylpenicillamine (SNAP) or interferon-gamma activated peritoneal macrophages. In both situations, evidence of cyst damage and death was observed by microscopy in over 77% of cysts after 3 days, indicating that intact hydatid cysts could be susceptible to a Th1 driven macrophage attack. A crude extract of the laminated layer from cysts was found to be able to reduce the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 29 publications
3
35
1
Order By: Relevance
“…This observation is explained by the phagocytosis of laminated layer fragments by mononuclear inflammatory cells (STEERS et al, 2001), which were found extensively in different cystic lesions. Therefore, complete or partial phagocytosis of the laminated layers may occur during the immune response in different hosts.…”
Section: Discussionmentioning
confidence: 95%
“…This observation is explained by the phagocytosis of laminated layer fragments by mononuclear inflammatory cells (STEERS et al, 2001), which were found extensively in different cystic lesions. Therefore, complete or partial phagocytosis of the laminated layers may occur during the immune response in different hosts.…”
Section: Discussionmentioning
confidence: 95%
“…On comparing cytokine profiles of the present study with those of alveolar echinococcosis (Wellinghausen et al, 1999;Shi et al, 2004), compable cytokine profiles were found in cystic versus alveolar echinococcosis, the parasitic agents being very similar but the clinical course very different. NO was not investigated in human CE but the interaction between hydatid cyst and NO was investigated in mice (Steers et al, 2001). NO was produced by macrophages from mice infected with E. multilocularis that resulted in immunosuppression and prolonged larval growth and survival (Dai & Gottstein, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although small amounts of NO are constitutively released by endothelial and neuronal nitric oxide enzymes, inducible NO, located mainly in immune cells such as macrophages, is induced and produced in considerable amounts after exposure to cytokines (Nussler et al, 1992;Lincolin et al, 1997). NO has been investigated in animal models of CE such as BALB/c mice (Steers et al, 2001). C-reactive protein (CRP) is an acute phase marker most commonly used to detect inflammation in the body and monitor the activity of a range of inflammatory conditions.…”
mentioning
confidence: 99%
“…Therefore, in the present study, the statistical significant higher levels of nitric oxide in group III, at 1st, 4th, 6th and 8th weeks post infection compared to group IV (Table 1) indicate the prophylactic and therapeutic effect of A. sativum in murine cystic hydatidosis. This protective effect of A. sativum could be mediated by nitric oxide production as, in vitro, murine hydatid cysts of E. granulosus were damaged and killed when incubated in presence of nitric oxide produced by IFN-c activated peritoneal macrophages (Steers et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In human elevated levels of NO and IFN-c have been observed in sera from some patients with E. granulosus infection (Touil-Boukoffa et al 1998). In vitro, murine hydatid cysts of E. granulosus were damaged and killed when incubated in presence of NO produced by IFN-c activated peritoneal macrophages (Steers et al 2001).…”
Section: Introductionmentioning
confidence: 99%